An experimental philosophical bioethical study of how human rights are applied to clitorectomy on infants identified as female and as intersex. Issue 4 (3rd February 2021) - Smith, Annette; Hegarty, Peter
Abstract: Clitorectomies performed on the genitals of infants identified as female and as intersex have been described both as similar procedures and as different procedures. The former types of surgery have been recognised more consistently as human rights abuses than the latter in recent decades. We tested social psychological explanations of why human rights are differently recognised when infants are described as 'intersex' or 'female'; 122 laypeople in the UK read one of two near-identical descriptions of clitorectomies performed on intersex or female infants and reported their agreement with 22 items about the human rights of such infants. Clitorectomies were perceived as violating human rights more by women than by men, and more so when infants were described as female than intersex. Endorsement of human rights was better predicted by several psychological variables when infants were described as female than as intersex. Less politically conservative participants, as assessed by a Right-Wing Authoritarianism measure, and participants who trusted medical authority more recognised human rights violations of female infants more than intersex infants. Results are discussed with respect to human rights efforts to protect infants from medically non-necessary genital surgery on the basis of membership in identity categories or possession of sex characteristics.